Efektivitas Self-Management Pasien Kanker di Rumah Sakit - Sopiah, Siti Herlina Ali; Waluyo, Agung; Afiyanti, Yati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of self-management carried out by cancer patients while in hospital. The method used was a systematic review of several databases, namely Proquest, Science Direct, Sage Pub, Scopus, Ebsco, ClicalKey Nursing, and PubMed, resulting in 15 articles that could be analyzed. The research results show that the self-management behavior that cancer patients can use to overcome symptoms during treatment in hospital is effective in its use, starting from managing symptoms of fatigue, severe pain, anxiety, the effects of specific diseases such as urinary elimination disorders, lymphedema, and mucositis. Conclusion: Strategies that can be used by patients to manage symptoms are by making lifestyle changes, including resting, reducing activity, changing diet, consuming supplements, reading books, doing light sports activities, yoga and meditation. These strategies are expected to improve the quality of life of cancer patients. who is in the hospital. Keywords: Cancer Patients, Hospitals, Self-Management